The Effect of Hypnotherapy using Induction Hanung Technique on the Level of Cigarette Dependence and Carbon Monoxide in Exhaled Breath among Active Smokers - Margiyati Margiyati; Meidiana Dwidiyanti; Diyan Yuli Wijayanti (Holistic Nursing and Health Science, 2018)
Background: Smoking is a habit that causes many health problems. Nicotine substances in cigarettes cause addiction and carbon monoxide inhaled is poisonous. Hypnotherapy using induction hanung technique is an alternative which can be used to change someone’s smoking behaviors. This therapy is performed by giving hypnotic suggestions combined with a massage at acupuncture points of neguan, yintang, and taiyang. Purpose: This study aimed to analyze the effects of hypnotherapy using induction hanung technique on the level of cigarette dependence and carbon monoxide in exhaled breath among active smokers in Kesdam IV/ Diponegoro College of Nursing, Semarang.Methods: The present study employed a true-experimental pretest-posttest control group design. A total of 40 students were recruited as samples and randomly assigned to the intervention group (n=20) and control group (n=20). The intervention in the form of hypnotherapy using induction hanung technique was given for six times in two weeks. The instruments used were Fagerstorm Test for Cigarette Dependence (FTCD) and smokerlyzer. Data were analyzed with the Mann-Whitney test and independent t-test.Results: The results showed a decrease in the score of cigarette dependence level in the intervention group by 1.25 after the intervention was given with pretest mean value of 1.45 (SD=1.132). The result of Mann-Whitney test showed a significant difference in the cigarette dependence score between the intervention and control groups with a pvalue of 0.028. The level of carbon monoxide in the exhaled breath also decreased by 8.80 ppm after the intervention from the pretest mean values of 12.55 (SD=6.669). The independent sample t-test result also showed a significant difference in the carbon monoxide level between the two groups with a p-value of 0.000.Conclusion: The present findings showed that hypnotherapy using induction hanung technique affected the level of cigarette dependence and carbon monoxide in exhaled breath among the active smokers. Based on the findings, this therapy is recommended as an alternative to nursing intervention for the smoking cessation programs.